2015
DOI: 10.1103/physrevb.92.014505
|View full text |Cite
|
Sign up to set email alerts
|

Resonant enhancement of macroscopic quantum tunneling in Josephson junctions: Influence of coherent two-level systems

Abstract: We report a theoretical study of the macroscopic quantum tunneling (MQT) in small Josephson junctions containing randomly distributed two-level systems. We focus on a Josephson phase escape for switching from the superconducting (the zero-voltage) state to a resistive one. Above the crossover temperature T cr the thermal fluctuations of the Josephson phase induce such a switching, and as T < T cr the regime of the MQT occurs. In the absence of two-level systems (TLSs) a magnetic field applied parallel to the j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Al/AlO x /Al Josephson junctions are the building blocks of a wide range of superconducting quantum devices that are key elements for quantum computers, extremely sensitive magnetometers and radiation detectors 1 2 3 . A fundamental limiting factor for the implementation of Josephson junction based superconducting quantum electronics is the coupling of the coherent quantum state with two-level systems (TLS) accommodated in the amorphous oxide material in the circuits, resulting in noise and decoherence 4 5 6 7 8 9 10 . The TLS in the insulating oxide barrier in Josephson junctions have been considered as a major source of energy dissipation and decoherence in superconducting electric circuits, especially in qubits 11 12 13 .…”
mentioning
confidence: 99%
“…Al/AlO x /Al Josephson junctions are the building blocks of a wide range of superconducting quantum devices that are key elements for quantum computers, extremely sensitive magnetometers and radiation detectors 1 2 3 . A fundamental limiting factor for the implementation of Josephson junction based superconducting quantum electronics is the coupling of the coherent quantum state with two-level systems (TLS) accommodated in the amorphous oxide material in the circuits, resulting in noise and decoherence 4 5 6 7 8 9 10 . The TLS in the insulating oxide barrier in Josephson junctions have been considered as a major source of energy dissipation and decoherence in superconducting electric circuits, especially in qubits 11 12 13 .…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] It has also been shown that Landau-Zener transition can enhance the resonant tunneling rate. [19][20][21] MRT has been used to prove that the low-frequency flux noise in both Josephson junctions and rf-SQUID system is the crucial source of quantum noise. [22][23][24][25][26] In this article, we experimentally demonstrate the observation of MRT between macroscopic distinct states in an rf-SQUID system, which is driven by an external single-cycle sinusoidal driving signal.…”
Section: Introductionmentioning
confidence: 99%